Efficient tandem aqueous room temperature oxidative amidations catalysed by supported Pd nanoparticles on graphene oxide. Issue 12 (27th January 2016) - Rostamnia, Sadegh; Doustkhah, Esmail; Golchin-Hosseini, Habib; Zeynizadeh, Behzad; Xin, Hongchuan; Luque, Rafael
Abstract : Pd nanoparticles deposited onto graphene oxide nanosheets (SE-GO/PdNPs ) were found to successfully promote two oxidative processes for the synthesis of amides, providing alternative possibilities to these important compounds. Abstract : Pd nanoparticles deposited onto graphene oxide nanosheets (SE-GO/PdNPs ) were found to successfully promote two oxidative processes for the synthesis of amides, providing alternative possibilities to these important compounds. SE-GO/PdNPs exhibited excellent activities with an optimum efficiency in tandem one-pot conversion of alcohols to amides in the presence of various amines.